Outlet Glacier and Landscape Evolution of Victoria Land, Antarctica - Whitmore, Ross (Victoria University of Wellington, 2020)
Terrestrial cosmogenic exposure studies are an established and rapidly evolving tool for landscapes in both polar and non-polar regions. This thesis takes a multifaceted approach to utilizing and enhancing terrestrial cosmogenic methods. The three main components of this work address method development, reconstructing surface-elevation-changes in two large Antarctic outlet glaciers, and evaluating bedrock erosion rates in Victoria Land, Antarctica. Each facet of this work is intended to enhance its respective field, as well as benefit the other sections of this thesis. Quartz purification is a necessary and critical step to producing robust and reproducible results in terrestrial cosmogenic nuclide studies. Previous quartz purification work has centred on relatively coarse sample material (1 mm-500 μm) and is effective down to 125 μm. However, sample material finer than that poses significant purification challenges and this material is usually discarded. The new purification procedure outlined in this thesis shows that very fine sand size material (125-63 μm) can be reliably cleaned for use in terrestrial cosmogenic nuclide studies. The results below show that 35% mass loss in very fine-grained quartz is sufficient to remove major elements (Al, Ti, Na, K, Fe, Mg, Ca, Mn,) and trace elements (9Be, and 10B) along with meteoric 10Be. Insufficient leaching is most detrimental to Al concentration, however errors up to 27% in exposure age and up to 29% in erosion rate are possible if meteoric 10Be is not fully removed from quartz during the HF leaching stages. Outlet glaciers have been well observed since the beginning of the satellite era, approximately 60 years ago. However, we do not currently know how these important glaciers, which drain a significant portion of the Antarctic Ice Sheet, have behaved on centennial to millennial timescales. Dating glacial erratics deposited by a thinning outlet glacier provides a window into the long-term outlet glacier and ice sheet response to climatic forcing. New results in ...